N-body chaos, phase-space transport and relaxation in numerical simulations. Issue Volume 14:Issue S351(2019) (May 2019) - Di Cintio, Pierfrancesco; Casetti, Lapo
Abstract: Using direct N -body simulations of self-gravitating systems we study the dependence of dynamical chaos on the system size N . We find that the N -body chaos quantified in terms of the largest Lyapunov exponent Λmax decreases with N . The values of its inverse (the so-called Lyapunov time t λ ) are found to be smaller than the two-body collisional relaxation time but larger than the typical violent relaxation time, thus suggesting the existence of another collective time scale connected to many-body chaos.